Dynamic Nonlinear and Residual Deformation Behaviors of the Fly Ash-Modified Loess - Qian Wang; Jun Wang; Xiumei Zhong; Haiping Ma; Xiaowei Xu (Shock and Vibration)
Metastable loess soils can deform, inducing geological and engineering disasters. Therefore, the behavior of the loess under dynamic load is gaining massive attention from researchers to improve the strength of the soils. Fly ash mixed with loess can improve strength and reduce construction costs and environmental pollution. Moreover, it has strong economic and social benefits. This paper investigates the influence of fly ash on the dynamic properties of the modified loess through a series of dynamic triaxial tests of the fly ash modified loess with different fly ash contents. The treated soil samples were prepared using a static compaction method in both ends and cured for 28 days. The dynamic shear modulus ratio, the damping ratio, and the dynamic residual strain of the modified loess were analyzed. The variation characteristics of the dynamic shear modulus ratio and damping ratio with the dynamic shear strain of the fly ash modified loess were obtained. The effect of fly ash content on the dynamic nonlinear parameters of the modified loess was also investigated. In addition, the relationship between the dynamic residual strain and the fly ash content was discussed. The results show that the dynamic shear modulus ratio of fly ash modified loess decreases nonlinearly with the increase in the dynamic shear strain. However, the attenuation rate difference of the curves is small. The damping ratio increases gradually with increasing dynamic shear strain. Under a certain dynamic shear strain level, the damping ratio decreases with the increase in the fly ash content. The dynamic residual strain increases with the increase in the dynamic stress. However, it decreases with the increase in the fly ash content. When the fly ash content is between 10% and 20%, the dynamic residual strain of fly ash modified loess is reduced rapidly. However, when the fly ash content exceeds 20%, the dynamic residual strain decreases slowly. The fly ash content of 20% could be suggested as an optimal content for seismic resistance of the loess foundation.